Burden eaudiobook - Felix, Lila (Bayou Bear Chronicles, 2020)
When their eyes meet, their hearts stop and beat as one. I've always been told I was the anomaly, the fluke, the only black bear they'd ever seen. Somehow, I know that's not true. The wolves have told me the Alpha over all the bears is headed this way. But they've sent me away so he won't see me. I'm a burden, a hindrance to the grizzlies, yet they keep a shock collar around my neck so I can't escape. On the wolf pack lands, I see someone approaching. A male—and he smells like home. Has someone come to save me?